VAMP5 and distinct sets of cognate Q-SNAREs mediate exosome release - Takahide Matsui; Yuriko Sakamaki; Shu Hiragi; Mitsunori Fukuda (Cell Structure and Function, 2023)
Small extracellular vesicles (sEVs) are largely classified into two types, plasma-membrane derived sEVs and endomembrane-derived sEVs. The latter type (referred to as exosomes herein) is originated from late endosomes or multivesicular bodies (MVBs). In order to release exosomes extracellularly, MVBs must fuse with the plasma membrane, not with lysosomes. In contrast to the mechanism responsible for MVB–lysosome fusion, the mechanism underlying the MVB–plasma membrane fusion is poorly understood. Here, we systematically analyze soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) family proteins and identify VAMP5 as an MVB-localized SNARE protein required for exosome release. Depletion of VAMP5 in HeLa cells impairs exosome release. Mechanistically, VAMP5 mediates exosome release by interacting with SNAP47 and plasma membrane SNARE Syntaxin 1 (STX1) or STX4 to release exosomes. VAMP5 is also found to mediate asymmetric exosome release from polarized Madin-Darby canine kidney (MDCK) epithelial cells through interaction with the distinct sets of Q-SNAREs, suggesting that VAMP5 is a general exosome regulator in both polarized cells and non-polarized cells. Key words: exosome, small extracellular vesicle (sEV), multivesicular body, SNARE, VAMP5